Ferulic Acid as Building Block for the Lipase-Catalyzed Synthesis of Biobased Aromatic Polyesters - Alfred Bazin; Luc Avérous; Eric Pollet (Polymers, 2021)
Enzymatic synthesis of aromatic biobased polyesters is a recent and rapidly expanding research field. However, the direct lipase-catalyzed synthesis of polyesters from ferulic acid has not yet been reported. In this work, various ferulic-based monomers were considered for their capability to undergo CALB-catalyzed polymerization. After conversion into diesters of different lengths, the CALB-catalyzed polymerization of these monomers with 1,4-butanediol resulted in short oligomers with a DPn up to 5. Hydrogenation of the double bond resulted in monomers allowing obtaining polyesters of higher molar masses with DPn up to 58 and Mw up to 33,100 g·mol−1. These polyesters presented good thermal resistance up to 350 °C and Tg up to 7 °C. Reduction of the ferulic-based diesters into diols allowed preserving the double bond and synthesizing polyesters with a DPn up to 19 and Mw up to 15,500 g·mol−1 and higher Tg (up to 21 °C). Thus, this study has shown that the monomer hydrogenation strategy proved to be the most promising route to achieve ferulic-based polyester chains of high DPn. This study also demonstrates for the first time that ferulic-based diols allow the synthesis of high Tg polyesters. Therefore, this is an important first step toward the synthesis of competitive biobased aromatic polyesters by enzymatic catalysis.